APPLICATION OF THE CREATIVE PROBLEM-SOLVING LEARNING MODEL TOWARDS STUDENTS' MATHEMATICS REPRESENTATION ABILITY - Firmansyah, Muhammad Arie; Pradja, Barra Purnama; Raharjo, Sigit; Aldi, Aldi (Prima: Jurnal Pendidikan Matematika, 2024)
This research aims to find out what the learning process is like using the Problem based learning model. Hypothesis testing using the t test shows that there is a significant difference, namely significant (2-tailed) 0.004 < 0.05 so it can be concluded that H0 is rejected and H1 is accepted. This means that there is an average difference in students' mathematical representation abilities between the experimental class and the control class. Thus, the results of this hypothesis test show that there is an influence of the Creative Problem-Solving learning model on students' mathematical representation abilities